Kearifan Lokal Berbasis Lingkungan dalam Tradisi Keagamaan sebagai Strategi Pemberdayaan Ekonomi Masyarakat - Umar Mukhtar Siregar; Hidayat Herman (Management Studies and Business journal, 2025)
This study examines how environmentally oriented local wisdom embedded in religious traditions can function as a strategy for community economic empowerment. Environmental degradation and rural economic vulnerability require approaches that integrate ecological sustainability with culturally legitimate economic practices. Using a qualitative case study design, data were collected through observation, in-depth interviews, and document analysis involving religious leaders, traditional authorities, and local micro-entrepreneurs. The findings reveal that religious traditions institutionalize ecological values through norms, rituals, and social sanctions that regulate natural resource use and shape production practices. These values generate social and symbolic capital that strengthens trust, collective action, and market legitimacy for environmentally friendly local products. However, economic pressures and market demands may weaken normative compliance when material incentives are absent. This study demonstrates that religious traditions are not merely symbolic cultural expressions but can be reconstructed as strategic resources for sustainable economic empowerment. The novelty of this research lies in conceptualizing religiously embedded local wisdom as an operational framework linking environmental ethics, social capital, and community-based economic practices. The study contributes to interdisciplinary debates on religion, local culture, and sustainable development by proposing an integrative model of value-based economic empowerment.